Awareness, Knowledge, and Perceptions Regarding Rabies Prevention Among Rural Communities in Masaka District, Central Uganda: A Qualitative Study - Kankya, Clovice; Dürr, Salome; Hartnack, Sonja; Warembourg, Charlotte; Okello, Justine; Muleme, James; Okello, Walter; Methodius, Tubihemukama; Alobo, Grace; Odoch, Terence (Frontiers in Veterinary Science, 2022)
Rabies is a zoonotic disease that is mainly transmitted to humans through dog bites. It remains a major public health threat in many Asian and African countries, including Uganda. The main objective of this study was to investigate awareness, knowledge, and perceptions of communities toward human and dog health related to rabies prevention, as well as dog management practices within Masaka district, central Uganda. Data collection involved nine key informant interviews (KIIs) and six focus group discussions (FGDs). Methods used during focus group discussions included qualitative interviews (using open-ended questions), simple ranking, and proportional piling. Data from KIIs and FGDs were analyzed using content analysis in NVivo (version 12.0). This study reveals that community members in the rural settings uses herbal concoctions in replacement or as an alternative to dog vaccination. Furthermore, the study reveals that dogs play the vital roles in the households like as they offer protection to people and household properties, despite being ranked second least among the household animals. The commonest livelihood activity was a small-scale mixed farming. Most of the households kept dogs, but they are ranked at second lowest in terms of economic value among all domestic animals. Free roaming and tethering were the common dog-keeping systems, and home-based feed (food leftovers, bones) was provided mainly to the tethered dogs. Rabies, also locally known as “Eddalu Lyembwa” (that can be translated as “madness of the dogs”), was ranked as the disease of most important among dogs, besides other common diseases such as skin diseases, venereal diseases, worm infestations, and tick infestations. Inadequate vaccination services for both humans and dogs were reported, and dog bite victims traveled a long distance to seek for post-exposure prophylaxis after dog bites. It can be concluded that there is a clear request for periodic mass vaccination campaigns against rabies among dogs, and access to vaccines within reasonable distances by humans after a rabies exposure, but also pre-emptive vaccination for those at high risk, such as veterinarians, needs to be improved.